2012
DOI: 10.1523/jneurosci.5586-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Period Coding of Bmal1 Oscillators in the Suprachiasmatic Nucleus

Abstract: Together with computer simulations, we show that either the intercellular coupling does not strongly influence the Bmal1 oscillation or the nature of the coupling is more complex than previously assumed. Furthermore, we have found that the region-specific periods are modulated by the light conditions that an animal is exposed to. Based on these, we suggest that the period forms the basis of seasonal coding in the SCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
124
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(135 citation statements)
references
References 54 publications
11
124
0
Order By: Relevance
“…S1). The period of the Bmal1-ELuc reporter oscillation in the SCN changes similarly to the change in behavioral period after day-length entrainment (12), similar to Per1 GFP rhythms in cultured SCNs after perinatal photoperiodic imprinting (24). Bioluminescence imaging revealed that the phase distribution of the cellular Bmal1-ELuc oscillations in the SCN becomes narrower after SD and wider after LD entrainment ( Fig.…”
Section: Representation Of Entrained Day Length In the Scn By Networkmentioning
confidence: 55%
See 2 more Smart Citations
“…S1). The period of the Bmal1-ELuc reporter oscillation in the SCN changes similarly to the change in behavioral period after day-length entrainment (12), similar to Per1 GFP rhythms in cultured SCNs after perinatal photoperiodic imprinting (24). Bioluminescence imaging revealed that the phase distribution of the cellular Bmal1-ELuc oscillations in the SCN becomes narrower after SD and wider after LD entrainment ( Fig.…”
Section: Representation Of Entrained Day Length In the Scn By Networkmentioning
confidence: 55%
“…When measured through a luciferase reporter monitoring oscillations in the Bmal1 gene, the D-SCN and V-SCN clusters show a phase gap, with the D-SCN leading the V-SCN. Although the D-SCN/V-SCN cluster structure is preserved across a moderate range of day length (8-16 h) (12), the phase gap increases with increasing day length (13). The mechanism for this phase gap remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During long days, however, SCN cells distribute their phase relationships more widely, so that they are less synchronized in their time of daily peak activity. This coincides with a depolarization in the equilibrium potential for GABA (i.e., chloride) (Myung et al 2012;Farajnia et al 2014). Consequently, GABA signaling has the potential to switch from low-frequency, inhibitory communication to higher-frequency, often excitatory, communication.…”
Section: Role Of Gaba: Modulating Synchrony With the Seasonsmentioning
confidence: 92%
“…Because this approach uses abstract limit cycle oscillators, which are not based on underlying molecular dynamics, the variables and parameters of those models are too abstract to compare with physical quantities. Nonetheless, these abstract models can provide important insight into experimental data on phase relationship of circadian rhythms, such as phase response to external signals [16][17][18], phase entrainment [19][20][21][22], and phase regulation via coupling signal [23][24][25][26]. Furthermore, such models have also been used recently to analyse the phase and amplitude information from circadian time-course data [27,28] and to investigate circadian regulation of other systems (e.g.…”
Section: Introductionmentioning
confidence: 99%